ASTRONOMIYA KURSIDAN AMALIY MASHG‘ULOTLARGA INNOVATSION TA’LIM TEXNOLOGIYALARI VA AXBOROT TEXNOLOGIYALARINI TATBIQ ETISH - Sayfullayeva, G.I. (SCIENCE and SOCIETY, 2023)
Since the 21st century is the age of information technologies, any teacher, including astronomy teacher, should develop information-communicative competence, so it is necessary to teach students to be able to receive information from various sources, for example, from electronic sources.